A cross sectional study to evaluate serum calcium levels among pregnant women and it’s association with preeclampsia and delivery outcomes at tertiary care Hospital Bikaner, Rajasthan - Poonia, Laxmi; Kochar, Swati; Chaudhary, Shweta; Gaur, Priyanka; Solanki, Kirti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Hypertensive disorders of pregnancy, including preeclampsia complicates about 10% of pregnancies worldwide. Preeclampsia is one of the major cause of maternal and perinatal morbidity and mortality worldwide. According to the National Health Portal of India, the incidence of preeclampsia is reported to be about 8-10% among pregnant women. The present study was aimed to compare mean serum calcium levels in preeclamptic and normotensive pregnant women at third trimester of gestation and assess relationship between maternal serum calcium levels, severity of disease and overall maternal and perinatal outcome. Methods: This was a cross sectional study conducted on 200 females divided into two groups (i.e. Study and Control Group) from 1st November 2019 to 31st October 2020. Informed consent was obtained for subjecting. Detailed history and clinical examination were performed. Serum calcium level was measured in both groups by spectrophotometric method. Results: Mean serum calcium level in study group (preeclamptic) was 7.84±0.74 mg/dl while in control group (normotensive) mean serum calcium level was 9.68±0.97 mg/dl. Serum calcium level was significantly lower in preeclamptic women than normotensive pregnant women (p<0.001).Serum calcium showed significant negative correlation with systolic and diastolic blood pressure. Conclusions: This study concludes that hypocalcaemia may have a role in aetiology of preeclampsia and adverse maternal and perinatal outcome. Thus intake of calcium supplements may help in reduction of incidence of preeclampsia especially in a population of a developing country.